The Dilemma of Constitutional Reform in Bosnia and Herzegovina : Discussing Options with a View to EU Accession - Sahadžić, Maja,; Sekulić, Tatjana,; Vranješ, Nevenko,; Woelk, Jens, (Human Rights and Humanitarian Law E-Books Online, Collection 2026., 2025)
This volume constitutes the first comprehensive examination of Bosnia and Herzegovina's complex constitutional architecture, authored by a group of distinguished scholars primarily affiliated with leading public universities in the country. Grounded in a two-year research project and scholarly dialogue, it engages critically with the foundational constitutional principles, institutional configurations, and territorial arrangements underpinning the post-Dayton constitutional order. Emphasizing the ongoing challenges of democratic consolidation and European integration, the book offers nuanced perspectives on the interplay between individual and collective rights, federal and consociational models, and multi-level governance. It represents a vital contribution to contemporary constitutional discourse in post-conflict societies.